Growth Regulator Indole-3-Butyric Acid on Rooting Potential of Actinidia deliciosa Rootstock and Actinidia arguta Female Scion Species Stem Cuttings - Mapogo Kgetjepe Sekhukhune; Yvonne Mmatshelo Maila (Horticulturae)
A study was conducted to access the effectiveness of exogenous application of indole-3-butyric acid (IBA) on adventitious root formation in kiwifruit semi-hardwood stem cuttings (SCs) from Actinidia deliciosa rootstock and Actinidia arguta female scion. Treatment comprised IBA concentrations of 0, 10, 100, 1000, 10,000 and 100,000 ppm. Parallel experiments for A. deliciosa and A. arguta’s treatment were arranged in a randomised complete block design, with 12 replications. In A. deliciosa, treatments had significant (p ≤ 0.05) effects in rooting percentage, number of roots, root length, size of callus formation and callus percentage, except for dry root mass. In A. arguta, treatments showed significant (p ≤ 0.05) effects in rooting percentage, number of roots, root length and dry root mass. No callus formation was observed in A. arguta. Relative to the control, in A. deliciosa, the highest (42%) rooting percentage and lengthy (0.301 cm) roots, were observed at 10,000 ppm IBA concentration, whereas the most (0.295) number of roots were produced at 100,000 ppm IBA concentration. Calli percentage (94%) was highest at 100 ppm IBA, while the size of callus formation was the biggest (2.8) at IBA concentration of 100,000 ppm, when compared to the control. In A. arguta, the highest (100%) rooting percentage was achieved at the control (0 ppm), 100 ppm and 10,000 ppm IBA concentrations, whereas the greatest (0.9815) number of roots were observed at the IBA concentration of 10 ppm. Lengthy (1.0839 cm) roots were achieved at IBA concentration of 100 ppm, whereas the greatest (0.1061 g) dry root mass was attained at IBA concentration of 10,000 ppm. In conclusion, the use of growth regulator IBA was effective for root formation in SCs of A. deliciosa rootstock. In A. arguta female scion, IBA application improved the quality of rooting (more and longer roots). IBA application showed its potential in stimulating root development at 10,000 ppm IBA.